Social and Psychophysiological Consequences of the COVID-19 Pandemic: An Extensive Literature Review - Clemente-Suárez, Vicente Javier; Dalamitros, Athanasios A.; Beltran-Velasco, Ana Isabel; Mielgo-Ayuso, Juan; Tornero-Aguilera, Jose Francisco (Frontiers in Psychology, 2020)
The actual Coronavirus Disease 2019 (COVID-19) pandemic has surprised health authorities around the world producing a global health crisis. Recent studies suggest that the effective measure taken to curb the spread of the COVID-19 outbreak has lead to generate burden throughout the population. Thus, it is necessary to establish and identify the possible risk factors related to the psychosocial and psychophysiological strain during the COVID-19 outbreak. The present extensive literature review asses the social, psychological, and physiological consequences of COVID-19, reviewing the impact of quarantine measures, isolation, vast human loss, social and financial consequences in the family's economies, and its impact on the psychological health of the population. We also discussed the effect of psychophysiological factors as the impact of physical inactivity and modifications in nutritional habits at psychological and physiological levels. The present review includes actualized to date bibliography, which articles were methodologically analyzed to verify they met the standards of quality and scientific accuracy. Authors understand the pandemic as a multifactorial event which only a profound and extensive analysis would lead to better compression and efficient intervention in the present future.